2021
DOI: 10.1002/ehf2.13242
|View full text |Cite
|
Sign up to set email alerts
|

Cardio‐microcurrent device for chronic heart failure: first‐in‐human clinical study

Abstract: Aims Most devices for treating ambulatory Class II and III heart failure are linked to electrical pulses. However, a steady electric potential gradient is also necessary for appropriate myocardial performance and may be disturbed by structural heart diseases. We investigated whether chronic application of electrical microcurrent to the heart is feasible and safe and improves cardiac performance. The results of this study should provide guidance for the design of a two-arm, randomized, controlled Phase II trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Furthermore, it is important to note that devices for electrical stimulation of organs with a weak constant electrical current are in clinical testing and have shown promising results [ 14 , 15 ]. There is, however, a dire need to understand the underlying mechanisms of how cells behave upon electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is important to note that devices for electrical stimulation of organs with a weak constant electrical current are in clinical testing and have shown promising results [ 14 , 15 ]. There is, however, a dire need to understand the underlying mechanisms of how cells behave upon electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies on rat hearts have shown that electric stimuli regulate the expression of ECM components and their inhibitors, accompanied by a significant decrease in pro-inflammatory cytokines [ 12 , 13 ]. Furthermore, recent studies with a Cardio-microcurrent device concluded that weak constant electrical current application to the heart is not only feasible and safe but also shows promising results in heart function and size [ 14 , 15 ]. Considering these promising outcomes observed with rat cardiomyocytes and preliminary clinical applications, this study specifically aimed to unveil the mechanism by which myofibroblasts respond to electrical stimulation to promote cardiac functional recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The C-MIC device is currently under investigation for clinical use within the first pilot study including 10 patients with nonischemic dilated cardiomyopathy. 9…”
Section: Discussionmentioning
confidence: 99%
“…A recently reported longitudinal study identified an increased left ventricular ejection fraction with a reduction in end-systolic and end-diastolic left ventricular size along with an increase in 6-min walk, NYHA functional class, and quality of life. 1 There is a rapid functional improvement that can be demonstrated after only a few hours of microcurrent application (Fig. 1).…”
mentioning
confidence: 95%
“…A recently reported longitudinal study identified an increased left ventricular ejection fraction with a reduction in end-systolic and end-diastolic left ventricular size along with an increase in 6-min walk, NYHA functional class, and quality of life. 1 …”
mentioning
confidence: 99%